The effect of 6% Hydroxyethyl starch vs. Ringer's lactate on acute kidney injury after renal ischemia in rats - Azevedo,Vera Lucia Fernandes de (2013)
PURPOSE: To compare fluid replacement therapy with Hydroxyethyl starch 6% (HES) versus Ringer's lactate (RL) in a rodent model of non-septic renal ischemia. METHODS: Forty male Wistar rats were randomized to receive HES 2 ml.kg-1.hr-1or RL 5 ml. kg-1.hr-1 that underwent 30 minutes of renal ischemia followed by reperfusion. Twelve hours after kidney ischemia, the kidneys were evaluated for histological changes. Serum NGAL levels were obtained at different times of the experimental protocol. RESULTS: Rodents in the HES group had a median (IQR) grade of renal injury 3 (3 to 5) compared to 2 (2 to 4) in the RL group (p=0.03). NGAL levels were not associated with the severity of kidney injury. CONCLUSION: Hydroxyethyl starch administration caused more kidney injury than Ringer's lactate in a non-infectious model of renal hypoperfusion.